2012
DOI: 10.1002/j.1875-9114.2012.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae Carbapenemases in Enterobacteriaceae: History, Evolution, and Microbiology Concerns

Abstract: Since the discovery of penicillin 80 years ago, gram-negative bacteria have become proficient at evading the lethal activity of β-lactam antibiotics, principally through the production of β-lactamases. The rapid emergence of penicillinases in both gram-positive and gram-negative bacteria led to the development of cephalosporin β-lactam antibiotics, but production of plasmid-mediated extended-spectrum cephalosporinases (or extended-spectrum β-lactamases) and AmpC enzymes resulted in resistance to this drug clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 82 publications
(117 reference statements)
0
43
0
5
Order By: Relevance
“…KPC gene was the predominant carbapenemase gene detected in this study. Although, KPC gene was reported to be the predominant carbapenemases among Enterobacteriaceae worldwide, [20] Spellberg and colleagues reported that NDM-1 was predominantly common in survey of Enterobacteriaceae they did in 2009 but in 2010 they reported KPC as the most predominant in UK [21].…”
Section: Discussionmentioning
confidence: 98%
“…KPC gene was the predominant carbapenemase gene detected in this study. Although, KPC gene was reported to be the predominant carbapenemases among Enterobacteriaceae worldwide, [20] Spellberg and colleagues reported that NDM-1 was predominantly common in survey of Enterobacteriaceae they did in 2009 but in 2010 they reported KPC as the most predominant in UK [21].…”
Section: Discussionmentioning
confidence: 98%
“…In Rapp and Urban (2012), most KPC-producing isolates had a carbapenem MIC ≥ 2 μg/ml, but some have been reported to be susceptible to carbapenems. The reason for this discrepancy is that full resistance to carbapenems usually requires the presence of a second mechanism of resistance such as a defect in the permeability of outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of penicillin 80 years ago, Gramnegative bacteria have become proficient at evading the lethal activity of β-lactam antibiotics, principally through the production of β-lactamases (Rapp and Urban, 2012 Beta-lactam antibiotics are a broad class of antibiotics, consisting of all antibiotic agents that contain a β-lactam ring in their molecular structures. This includes penicillin derivatives (penams), cephalosporins (cephems), monobactams and carbapenems (Holten and Onusko, 2000).…”
Section: Introductionmentioning
confidence: 99%